Influence of Reaction Temperature on Bioethanol Production by Saccharomyces Cerevisiae Using Cassava as Substrate - A. A, Musa; F.B, Salim; G.P, Shiaka; M, Muhammad; B, Nafisa; M.M, Surayya; A.Y, Sa’adatu; S. D, Hauwa; R, Gayus; A.M, Gumel (International Journal of Sustainable Energy and Environmental Research, 2021)
The alarming awareness and increasing concern over effect of global warming, and environmental pollution due to the continuous combustion of fossil fuels has necessitated the call for an alternative renewable energy. The trepidation on the sustainability of the global food supply due to emphasis on corn production to meet the increased demand for bioethanol led to the need to assess the potential of alternative crops as sources of bioethanol production. On this focus, cassava proved to be an ideal crop to fulfil this need as it is more abundant and meeting requirement in serving both edible and nonedible usage than corn. However, the yield and quality of bioethanol produced from cassava can be impacted by alteration of temperature during production process. From this research, production of bioethanol from cassava was found to be optimum at a temperature of 35°C, with maximum yield of 95% and any increase beyond 40°C leads to the gelatinization of starch. The research has stroke a balance at where and when temperature needs to be altered to increase yield.